The PIF1-miR408-PLANTACYANIN repression cascade regulates light-dependent seed germination. Issue 5 (22nd February 2021) - Jiang, Anlong; Guo, Zhonglong; Pan, Jiawei; Yang, Yanzhi; Zhuang, Yan; Zuo, Daqing; Hao, Chen; Gao, Zhaoxu; Xin, Peiyong; Chu, Jinfang; Zhong, Shangwei; Li, Lei
Abstract: Light-dependent seed germination is a vital process for many seed plants. A decisive event in light-induced germination is degradation of the central repressor PHYTOCHROME INTERACTING FACTOR 1 (PIF1). The balance between gibberellic acid (GA) and abscisic acid (ABA) helps to control germination. However, the cellular mechanisms linking PIF1 turnover to hormonal balancing remain elusive. Here, employing far-red light-induced Arabidopsis thaliana seed germination as the experimental system, we identified PLANTACYANIN (PCY) as an inhibitor of germination. It is a blue copper protein associated with the vacuole that is both highly expressed in mature seeds and rapidly silenced during germination. Molecular analyses showed that PIF1 binds to the miR408 promoter and represses miR408 accumulation. This in turn posttranscriptionally modulates PCY abundance, forming the PIF1-miR408-PCY repression cascade for translating PIF1 turnover to PCY turnover during early germination. Genetic analysis, RNA-sequencing, and hormone quantification revealed that PCY is necessary and sufficient to maintain the PIF1-mediated seed transcriptome and the low-GA-high-ABA state. Furthermore, we found that PCY domain organization and regulation by miR408 are conserved features in seed plants. These results revealed a cellular mechanism whereby PIF1-relayed external light signals are converted through PCY turnover to internal hormonal profiles for controlling seed germination. Abstract : The conserved blue copper protein PLANTACYANIN is regulated by PIF1 and miR408 to balance the ratio of gibberellic acid and abscisic acid which regulates far-red light dependent seed germination.